2003
DOI: 10.1111/j.1748-7692.2003.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Harbor Porpoises in the Kattegat and Skagerrak Seas: Accounting for Individual Variation and Sample Size

Abstract: Stomach contents of 112 bycaught harbor porpoises (Phocoena phocoena) collected between 1989 and 1996 in the Kattegat and Skagerrak seas were analyzed to describe diet composition and estimate prey size, to examine sample size requirements, and to compare juvenile and adult diets. Although porpoises preyed on a variety of species, only a few contributed substantially to the diet. Atlantic herring (Clupea harengus) was the dominating prey species for both juveniles and adults. Our results, in combination with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
2
39
1
1
Order By: Relevance
“…Stomach content analyses of harbour porpoises from the population inhabiting Skagerrak and the Kattegat have shown that herring, Atlantic cod, gobies and whiting are among the most important prey species (Aarefjord et al 1995, Börjesson et al 2003. Still, many other fish species, such as sandeel, sprat Sprattus sprattus, saithe, etc., were also found in lower numbers, showing that porpoises are preying on a large variety of species (Aarefjord et al 1995, Börjesson et al 2003, Sveegaard et al 2012a. Following this, it seems likely that the observed fish species at Laesø Trindel would be of interest to porpoises in the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomach content analyses of harbour porpoises from the population inhabiting Skagerrak and the Kattegat have shown that herring, Atlantic cod, gobies and whiting are among the most important prey species (Aarefjord et al 1995, Börjesson et al 2003. Still, many other fish species, such as sandeel, sprat Sprattus sprattus, saithe, etc., were also found in lower numbers, showing that porpoises are preying on a large variety of species (Aarefjord et al 1995, Börjesson et al 2003, Sveegaard et al 2012a. Following this, it seems likely that the observed fish species at Laesø Trindel would be of interest to porpoises in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Sveegaard et al (2012b) showed that the spatial distribution of harbour porpoises in the northern Kattegat and Skagerrak appears to be correlated with the distribution of herring Clupea harengus. Herring is an important prey species for porpoises in this area, together with Atlantic cod Gadus morhua, gobies (Family: Gobiidae) and whiting Merlangius merlangus (Aarefjord et al 1995, Börjesson et al 2003, Sveegaard et al 2012a. Porpoise abundance has also been linked to physical para meters, such as tidal phase, local hydrographic fronts and steep sea-bottom topography in combination with strong currents, as these features often lead to aggregation of prey (Johnston et al 2005, Goodwin 2008, Pierpoint 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size of 53 stomachs used in this study is comparable to the sample size in other studies in adjacent areas. Aarefjord et al (1995) also found thirteen species during the examination of forty porpoise stomachs in Kattegat, Lick (1991Lick ( , 1994Lick ( , 1995 found eight species in the German Baltic (62 porpoise stomachs), whereas Börjesson et al (2003) found twenty species in Kattegat and Skagerrak (112 porpoise stomachs). This indicates a decline in species diversity from the North Sea and Skagerrak to the Baltic Sea possibly following the gradient in salinity.…”
Section: Figmentioning
confidence: 98%
“…However, our sample size was reduced by the stratiWcation into seasons, and the sample size for the high season is nearly twice as high as during the low season. Börjesson et al (2003) estimated that approximately 35 stomach samples were the minimum sample size in Skagerrak and Kattegat needed to obtain all prey species with relative frequencies ¸10% with 95% conWdence. Consequently, our 34 samples from the high-density season are suYcient, but the 19 samples in the low density may result in species being underrepresented or missing.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation